Korelasi Implementasi Kurikulum Merdeka Dan Platform Merdeka Mengajar Dengan Kompetensi Profesional Guru Di Sekolah Dasar Negeri - Ristianni, Hajar; Yuliejantiningsih, Yovitha; Prayito, Muhammad (Jayapangus Press, 2025)
Competence is defined as knowledge, skills, and abilities mastered by a person who has become part of himself so that he can carry out cognitive, affective, and psychomotor behaviors as well as possible. The purpose of this study is to: 1) ascertain the magnitude of the influence of the implementation of the independent curriculum on teacher professional competence, 2) ascertain the magnitude of the influence of the independent teaching platform on teacher professional competence, and 3) ascertain the magnitude of the influence of the implementation of the independent curriculum and the independent teaching platform collectively on teacher professional competence. The research approach employed in this study is quantitative. The type of research conducted is correlational research. The research population comprised 377 teachers, from which a research sample of 194 teachers was determined. Data collection was executed through the administration of a questionnaire. The data analysis techniques utilized encompassed descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, and hypothesis tests comprising simple and multiple linear regression. The results of the study are: 1) The effect of the implementation of the independent curriculum has a significant and strong effect on the variable of teacher professional competence by 69.4%. 2) The effect of the independent teaching platform has a significant and strong effect on the variable of teacher professional competence by 69.5%. 3) The significant influence of X1, and X2 on Y is 86.5%. The conclusion drawn from this study indicates that the significant influence of the implementation of the independent curriculum and the independent teaching platform on teacher professional competence is 86.5%.